Effect of Cadmium Chloride on the weight of body and some organs of Japanese quail and the protective role of Quercetin - Taha, meer M.; Mohammed, Hind A. (International Journal of Scientific Research in Biological Sciences, 2023)
The current study wanted to know the effects caused by cadmium chloride in the body weight and the weight of some organs of the Japanese quail Coturnix coturnix japonica , which are the liver, kidney, and brain and the protective role of quercetin against these changes. In this study, (75) quail birds were used, and the birds were randomly divided into five experimental groups. The first group: which is the control group, was given distilled water for 45 days. The second group: the acute treatment group, was dosed with cadmium chloride at a concentration of 50 mg/kg for four consecutive days. The third group: the chronic treatment group, was dosed with cadmium chloride at a concentration of 20 mg/kg for 30 days. The fourth group: the quercetin group, was dosed with quercetin at a concentration of 50 mg/kg for 30 days, while the fifth group: which is the interference group, was dosed with quercetin at a concentration of 50 mg/kg for 45 days and within this period it was dosed with cadmium chloride at a concentration of 20 mg/kg for 30 days. The birds were dissected 4, 15, 30, and 60 days after the start of the experiment, and the birds were weighed before the start of the experiment and before each dissection, and the studied organs were weighed immediately after the dissection. The statistical results showed that there was a significant increase in the weight of the birds in the interference group compared to the control group as well as the rest of the groups. While the weight of the liver and kidney was significantly higher in the acute treatment group than the rest of the groups. While the brain weight was significantly higher in the quercetin group than the rest of the groups.